Influência de distúrbios causados por pisoteio e ressacas marítimas em uma população de Ocypode quadrata em praia urbanizada do litoral do Estado De São Paulo - Oliveira, Fernanda Ramos Fernandes de [UNIFESP] (2018)
The sandy beach ecosystem is constantly impacted by several disturbances such as trampling and storm surges, there is a need to understand how organisms react to these changes. One of the alternatives to evaluate such effects is a continuous monitoring of populations, that allows to evaluate their resilience to these disorders. The ghost crab Ocypode quadrata, common inhabitant of sandy beaches, is a bioindicator of anthropic and natural impacts in these environments. In this sense, the present work continuous monitoring (weekly) a population of O. quadrata in an area of urbanized beach for 57 weeks and, in an adjacent vegetal area by 6 weeks. The second monitoring was carried out in order to verify the relation between vegetation and the crustacean. The population of O. quadrata responded quickly to disturbances (storm surges and trampling), however in different ways. With regard to abundance, it was observed that (1) storm surges disturbs caused a decrease in population, (2) sporadic events of trampling caused an increase in abundance due to greater availability of food and (3) frequent trampling events reduced size populational. It was observed that O. quadrata prefers to construct it’s burrows in vegetated areas than in regions without any vegetation cover, due to the protection and stability that the vegetation offers to the burrows. Juveniles and recruits were observed in most months, suggesting a continuous reproduction of the species. Thus, on sandy beaches located in urbanized regions, the existence of protected areas (preferably with vegetation cover) favors the survival of the species, which can recover after episodes of abundance decrease. Under these conditions, the population of O. quadrata is more likely to adapt to adverse conditions and recover after the disturbances.